ISLAM DAN KEKERASAN: Perspektif Alquran tentang Persekusi di Indonesia - Khoiri, Ahmad; Windariana, Rofiatul (Islamuna: Jurnal Studi Islam, 2019)
The persecution was transformed as a new round of complicated problems which, among other things, were caused by religious exclusivism. In the Indonesian context, religion which should accommodate harmony in the midst of religious plurality is actually used as an excuse that is engineered to launch immoral acts such as persecution. This research aims to answer three main issues, namely the Islamic view of violence as a substantive part of persecution, the relationship of the case of persecutions with offense engineering, and the Quran’s view of persecution. With the Quranic interpretation and phenomenological approach, this study investigated three cases of persecution which attracted controversy, namely a case of persecution of Fiera Lovita, a doctor in Solok, West Sumatra, a persecution case against Abdul Somad, a famous dai, and a case of persecution of Khalid Basalamah, a Wahabi figure in Indonesia. This study succeeded in revealing that persecution was contrary to Islamic teachings, especially the Quran, and the three sample cases indicated that persecution was more a result of the accumulation of engineered ignorance rather than defending Islam, so that it must be stopped so that Indonesia would return to peace.[Persekusi menjelma sebagai babak baru persoalan pelik yang, di antaranya, disebabkan oleh ekslusivisme agama. Dalam konteks Indonesia, agama yang seharusnya mengakomodasi kerukunan di tengah pluralitas beragama justru dijadikan sebagai dalih yang direkayasa untuk melancarkan tindakan amoral semacam persekusi. Penelitian ini hendak menjawab tiga persoalan utama, yaitu pandangan Islam tentang kekerasan sebagai bagian substantif dari persekusi, hubungan kasus perseksusi dengan rekayasa ketersinggungan, dan pandangan Alquran tentang persekusi. Dengan pendekatan tafsir dan fenomenologi, penelitian ini menyelisik tiga kasus persekusi yang menuai kontroversi, yaitu kasus persekusi terhadap Fiera Lovita, seorang dokter di Solok, Sumatra Barat, kasus persekusi terhadap Abdul Somad, seorang dai kondang, dan kasus persekusi terhadap Khalid Basalamah, seorang tokoh Wahabi di Indonesia. Penelitian ini berhasil mengungkap bahwa persekusi bertentangan dengan ajaran Islam, terutama Alquran, dan tiga sampel kasus tersebut mengisyaratkan bahwa persekusi lebih merupakan hasil akumulasi rekayasa keterhasutan-ketersinggungan daripada membela Islam, sehingga harus dihentikan agar Indonesia kembali tenteram]